Khauf as a Moral Alarm : Suara Pelaku Yang Berjuang Melawan Perilaku PMO (Porn, Masturbation, Orgasm) - Maharani Tyas Budi Hapsari; Fitri Yusmia (Program Studi Psikologi Islam, 2025)
PMO (Porn, Masturbation, Orgasm) is often triggered by internal (stress, insomnia, fantasy, spirituality) and external (access to pornography, attraction to the opposite sex) motives. In Islam, khauf is a mental attitude that reflects fear of Allah SWT due to the awareness of imperfection in devotion to Him. According to Imam Al-Ghazali, it includes aspects of knowledge, aspects of hal (state of the heart), and aspects of charity. This study aims to explore more deeply the subjective experiences of PMO perpetrators who use Khauf as a mechanism for awareness of moral alarm and motivation for behavioral change. The method used in this study is a qualitative method with a phenomenological approach. Data collection used by researchers is semi-structured interviews, observation, and documentation. Data analysis model Miles and Huberman. The initial survey conducted by researchers showed that there were 30 respondents, it was found that PMO perpetrators were dominated by men with a percentage of 90% and 10% women. Fifty percent of users engage in PMO three times a week, 33.3% engage in PMO once a week, and 16.7% engage in PMO daily. Factors contributing to PMO include spiritual factors, psychological factors, social environment, education and information, and habits. The study found that khauf (awareness) is a method of managing emotions through a spiritual approach, moral awareness, developing healthy coping strategies, and strengthening support systems for monitoring.